Closeness to Parents Scale for Adolescence - Wulan Dewi Fatikhatus Syaidah; Devi Kusuma Wati; Urmilla Fakhrun Nisaa; Jasmine Nabila Maharani; Desy Enawaty; Erna Setiyani; R Anisa P S; Aftina Nurul Husna (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
The purpose of this study was to develop an instrument for the closeness of children with their parents. Proximity describes the form of a reciprocal relationship, namely mutual influence between parents and children. Aspects of closeness are emotional bonding, openness, the role of parents, respect, support, and figure. The scale development stage begins with collecting theories regarding the general closeness and closeness of children to parents. This sample uses a snowball random sampling technique. The development of instrument items is based on expert judgment using a Likert scale. The item design of the instrument consists of 75 statement items. Then after analyzing the assessment by the expert by determining the scale value and quality of the statement items, 20 selected statement items were produced. In the development, the researchers used respondents in the form of adolescents aged 16-19 years with the number of successfully collected n = 80. Researchers used validity and reliability tests to determine whether the items made were valid and reliable. The results of this study found Cronbach's alpha with a total of 20 items of 0.917. In conclusion, from the results of these calculations it can be seen that the closeness of children with parents is very good.